1999
DOI: 10.1002/(sici)1521-4141(199909)29:09<2769::aid-immu2769>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Human peripheral blood contains two distinct lineages of dendritic cells

Abstract: Human peripheral blood contains two populations of dendritic cells (DC) but their developmental relationship has not been established. Freshly isolated CD11c– DC possessed a lymphoid morphology, lacked myeloid markers but expressed lymphoid markers (CD4+ CD10+) whilst the CD11c+ DC were monocytoid in appearance and expressed myeloid markers. Although both populations were allostimulatory, only the CD11c+ DC were able to take up antigen. Irrespective of the culture conditions the CD11c– cells developed into CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
255
1
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(270 citation statements)
references
References 38 publications
9
255
1
5
Order By: Relevance
“…We applied flow cytometric methods that allow the enumeration and the immunophenotypical as well as functional characterisation of DCs directly in whole peripheral blood samples (Robinson et al, 1999;Arpinati et al, 2000;Upham et al, 2000). With this method, we observed that Lin-/HLA-DR þ DCs are significantly reduced in the peripheral blood of breast cancer patients compared with healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied flow cytometric methods that allow the enumeration and the immunophenotypical as well as functional characterisation of DCs directly in whole peripheral blood samples (Robinson et al, 1999;Arpinati et al, 2000;Upham et al, 2000). With this method, we observed that Lin-/HLA-DR þ DCs are significantly reduced in the peripheral blood of breast cancer patients compared with healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the significance of the increase of PB CD34 þ cells in breast cancer patients, ongoing studies are planned to characterise the immunophenotype and the functional activity of these cells in our patients. Since human PB DCs can be divided, on the basis of expression of the b-integrin CD11c (Robinson et al, 1999), into two subpopulations that differ in the origin, expression of phenotypic markers, route of activation and immunological activity, we evaluated their distribution in our patients. We found that the number of myeloid DCs, and not plasmacytoid DCs, was significantly decreased in breast cancer patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may result in an inefficient adaptive response against pyogenic bacteria, but augment the innate response against these microogranisms. Other factors present in BM CSF, for instance M-CSF [37], may also convert myeloid DC into macrophages [38]. In LM CSF, on the other hand, myeloid DC are abundant (up to 5000 cells/ml) [13], levels of IL-10 are relatively low, and IFN-g is present, augmenting production of IL-12 by myeloid DC.…”
Section: Discussionmentioning
confidence: 99%
“…At least two subsets of DCs were originally identified in peripheral blood, including myeloid DCs (mDCs) and plasmacytoid DCs (pDCs). [3][4][5][6] The mDCs express CD11c and CD1c (BDCA-1) antigens. In contrast, pDCs express CD123, BDCA-2 and BDCA-4 antigens.…”
Section: Introductionmentioning
confidence: 99%